Use of Geo-Information System in Creating Topological Maps (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
The article provides information on the use of GIS in the creation of land use maps using modern technologies for increasing, restoring, assessing and managing the productivity of irriGISed agricultural lands, including space imagery, geoinformation technologies and automated databases.